1993
DOI: 10.1177/106002809302700510
|View full text |Cite
|
Sign up to set email alerts
|

Valproate-Induced Coma: Case Report and Literature Review

Abstract: VPA-induced coma with hyperammonemia and without evidence of hepatic failure should be considered in patients being treated with PHT or PB when VPA is administered concomitantly. This case report shows the importance of clinical monitoring and immediate drug discontinuation when drowsiness, gastrointestinal symptoms, or lethargy occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 23 publications
0
67
0
2
Order By: Relevance
“…VHE sometimes occurs with normal liver enzyme serum levels and hepatic function (2,3). It can occur immediately after large loading doses of VPA or more insidiously over time, often in a level-or dose-related fashion (2,4).…”
mentioning
confidence: 99%
“…VHE sometimes occurs with normal liver enzyme serum levels and hepatic function (2,3). It can occur immediately after large loading doses of VPA or more insidiously over time, often in a level-or dose-related fashion (2,4).…”
mentioning
confidence: 99%
“…Aunque controvertido, el rango terapéutico se encuentra comprendido entre 50 y 100 µg/ml 66 . El 90% está unido a proteínas plasmáticas, aunque esta relación es dependiente de la concentración sérica, siendo del 81,5% para niveles de 130 mg/ml y de tan solo el 35% cuando se superan los 300 µg/ml 67 .…”
Section: Farmacocinética Y Farmacodinamiaunclassified
“…Although the incidence of hyperammonemia associated with hepatic encephalopathy is over 90% in the United States, elevated serum ammonia can be seen in patients therapeutically taking VPA or after a VPA overdose without any evidence of hepatic injury or failure [30,42,64,65]. Duarte et al reported a case of a 46-year-old woman who developed isolated hyperammonemia without any evidence of hepatic failure after being started on the drug [33]. VPA can cause elevation of serum ammonia by various, distinct pathways.…”
Section: What Occurs With Valproic Acid Toxicity?mentioning
confidence: 99%
“…In rat models, the metabolite 4-en-VPA causes microvesicular steatosis in the liver [62]. The concomitant use of phenobarbital therapy with VPA has been shown to induce the cytosolic -oxidation pathway and further increase the risk of hepatoxicity [33,63].…”
Section: What Occurs With Valproic Acid Toxicity?mentioning
confidence: 99%
See 1 more Smart Citation